Effect and clinical mechanism exploration of acupuncture intervention for chemotherapy-related cognitive impairment (CRCI) in triple-negative breast cancer: study protocol for a randomized controlled trial - Wenqi Yang; Wenqi Yang; Qing Zhang; Chong Gao; Jingzhi Zhang; Jingzhi Zhang; Xingwei Guo; Xingwei Guo; Xin Liu; Xin Liu (Frontiers in Neurology)
BackgroundChemotherapy-Related Cognitive Impairment (CRCI) significantly impacts the quality of life of breast cancer patients. Triple-negative breast cancer (TNBC) is associated with a higher risk of cognitive decline. The occurrence of CRCI is linked to the expression of inflammatory cytokines. Currently, limited research has examined the efficacy of acupuncture for treating CRCI in TNBC patients. This randomized controlled trial aims to evaluate the effectiveness of acupuncture in managing CRCI among TNBC patients and explore the mechanism by which acupuncture treatment affects CRCI through the inflammatory signaling pathway.MethodsThis study is designed as a prospective, parallel, randomized, sham-controlled, assessor-blinded clinical trial. It will involve 50 patients diagnosed with TNBC who also experience CRCI. Participants will be randomly assigned to two groups, with an equal 1:1 allocation ratio into either the intervention group or the control group. Both groups will receive acupuncture sessions twice weekly for 8 weeks, with each session lasting approximately 20 min. The primary outcome of this study will be the percentage of subjects showing improvement in the Montreal Cognitive Assessment (MoCA) score at the end of treatment. Secondary outcome measures will include the Mini-Mental State Examination (MMSE) score, EORTC QLQ-C30 score, and the expression of inflammatory cytokines.DiscussionThe findings of this study are expected to provide additional evidence supporting the efficacy of acupuncture and contribute clinical data that may elucidate the potential therapeutic mechanisms by which acupuncture ameliorates CRCI.Trial registrationhttps://www.chictr.org.cn/showproj.html?proj=218356, identifier: ChiCTR2400080147.